2013
DOI: 10.1155/2013/423254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Oxidation on the Conformational Properties of Peanut Protein Isolate

Abstract: Peanut protein isolate (PPI) was oxidized by peroxyl radicals derived from 2,2′-azobis (2-amidinopropane) dihydrochloride (AAPH), and the conformational properties of oxidized PPI were investigated. Oxidation of PPI resulted in gradual carbonyl generation and free sulfydryl group degradation. The analysis of the maximum emission wavelength indicated change in the tertiary conformation of PPI after oxidation. Lower level oxidation could generate soluble protein aggregates with more flexible structure, while hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
6
20
0
Order By: Relevance
“…Effect of protein oxidation on their emulsifying properties might be governed by their molecular structure and physicochemical characteristics. Oxidative characteristics of the AAPH-pretreated PPI had been reported by our former study (Ye et al, 2013). The investigation noticed that by incubating with increasing AAPH concentration, PPI oxidation extent enhanced, accompanied by a decreasing surface hydrophobicity and formation of soluble aggregates.…”
Section: Emulsifying Characteristics Of Oxidized Ppisupporting
confidence: 63%
See 2 more Smart Citations
“…Effect of protein oxidation on their emulsifying properties might be governed by their molecular structure and physicochemical characteristics. Oxidative characteristics of the AAPH-pretreated PPI had been reported by our former study (Ye et al, 2013). The investigation noticed that by incubating with increasing AAPH concentration, PPI oxidation extent enhanced, accompanied by a decreasing surface hydrophobicity and formation of soluble aggregates.…”
Section: Emulsifying Characteristics Of Oxidized Ppisupporting
confidence: 63%
“…The protein can be attacked directly by reactive oxygen species or indirectly by reaction with the by-products of lipid peroxidation, resulting in a number of changes in amino acid residue side chains and protein polypeptide backbone (Shacter, 2000). Therefore, conformation of protein under oxidative stress would change, which has also been observed by many former studies (Wu, Wu, & Hua, 2010;Wu, Zhang, Kong, & Hua, 2009;Ye, Liao, Zhao, & Sun, 2013). As protein emulsifying properties are closely related with its structure, protein oxidation would affect its emulsifying properties.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While for the Air plasma the Hb or Mb size is approximately the same as control. The increase in size of Hb and Mb is due to protein aggregation, the other groups 49 50 51 also supported this data that protein size increases due to protein aggregation that is the result of protein oxidation. Hence, this further provides an evidence that the oxidation or modification of protein are in control way, for Air plasma treatment as compared to other gases treatment.…”
Section: Resultsmentioning
confidence: 56%
“…While, control oxidation increase the bandwidth of BSA 48 . Recently published work by Ye et al 50 , observed that lower level of oxidation (carbonylation) could generate soluble protein aggregates that having less particle size. Whereas, higher level of oxidation would induce insoluble aggregates of protein, that results in higher molecular size.…”
Section: Discussionmentioning
confidence: 99%